2024
DOI: 10.1111/jpy.13431
|View full text |Cite
|
Sign up to set email alerts
|

How many species of algae are there? A reprise. Four kingdoms, 14 phyla, 63 classes and still growing

Michael D. Guiry

Abstract: To date (1 November 2023), the online database AlgaeBase has documented 50,589 species of living algae and 10,556 fossil species here referred to four kingdoms (Eubacteria, Chromista, Plantae, and Protozoa), 14 phyla, and 63 classes. The algae are the third most speciose grouping of plant‐like after the flowering plants (≈382,000 species) and fungi (≈170,000 species, including lichens) but are the least well defined of all the botanical groupings. Priority is given to phyla and class names that are familiar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Those algal OTUs, unannotated against SILVA, were further searched against the NCBI database ( https://www.ncbi.nlm.nih.gov/ , searched in September 2023) using BLAST with a percent identity cutoff 97% and an e-value cutoff close to zero (≤10 −30 ). The classification of algae was according to the up-to-date system suggested by Guiry (2024) and the AlgaeBase ( Guiry and Guiry, 2024 ). HAB and/or bloom species were confirmed in the online version of the IOC-UNESCO Taxonomic Reference List of Harmful Micro Algae ( Lundholm et al, 2009 ) or had been reported as a HAB or bloom species in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Those algal OTUs, unannotated against SILVA, were further searched against the NCBI database ( https://www.ncbi.nlm.nih.gov/ , searched in September 2023) using BLAST with a percent identity cutoff 97% and an e-value cutoff close to zero (≤10 −30 ). The classification of algae was according to the up-to-date system suggested by Guiry (2024) and the AlgaeBase ( Guiry and Guiry, 2024 ). HAB and/or bloom species were confirmed in the online version of the IOC-UNESCO Taxonomic Reference List of Harmful Micro Algae ( Lundholm et al, 2009 ) or had been reported as a HAB or bloom species in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…The term microalgae is traditionally used to describe photosynthetic eukaryotic microorganisms, including cyanobacteria [1] [2]. These microorganisms represent a significant biodiversity resource in terms of species number, morphology, biochemical pathways, but also in terms of ecological roles and applications [3]. All microalgae are autotrophs that photosynthesize through their pigments using them as light-harvesting molecules.…”
Section: Introductionmentioning
confidence: 99%
“…According to the AlgaeBase, 50,589 species of living algae and 10,556 fossil species are documented, referred to four kingdoms (Eubacteria Woese & Fox, 1977; Chromista Cavalier-Smith, 1981; Plantae Haeckel, 1866; and Protozoa Goldfuss, 1818), 14 phyla, and 63 classes [1]. Algae are the third most speciose grouping of plant-like after the flowering plants (≈382,000 species) and fungi (≈170,000 species, including lichens) [1].…”
Section: Introductionmentioning
confidence: 99%
“…According to the AlgaeBase, 50,589 species of living algae and 10,556 fossil species are documented, referred to four kingdoms (Eubacteria Woese & Fox, 1977; Chromista Cavalier-Smith, 1981; Plantae Haeckel, 1866; and Protozoa Goldfuss, 1818), 14 phyla, and 63 classes [1]. Algae are the third most speciose grouping of plant-like after the flowering plants (≈382,000 species) and fungi (≈170,000 species, including lichens) [1]. The most species-rich phylum is the golden and brown algae Heterokontophyta Moestrup, 1992 with 18 classes and 21,052 living species dominated by the diatoms class Bacillariophyceae Dangeard, 1933 with 18,673 species (16,427 living species and 2,239 fossil) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation